Assessment of the Risk of Pressure Ulcer During the Perioperative Period: Adaptation of the Munro Scale to Turkish - GÜL, ASİYE; Şengül, Tuba; Yavuz, Hafize Özge (Elsevier Science Ltd., 2021)
Aim of the study: This study was conducted to adapt the Munro Pressure Ulcer Risk Assessment Scale (Munro Scale) to Turkish and to test its validity and reliability. Materials and methods: In the methodological study, the data were collected using the patient identification form, the Braden Scale, and the Munro Scale. A total of 188 patients were diagnosed for the risk of preoperative and intraoperative pressure ulcer, and then re-evaluated in the recovery room and in their bed. Results: The study group consisted of 81 (43.1%) males and 107 (56.9%) females with a mean age of 51.98 ± 16.87. The Kaiser-Meyer-Olkin sampling adequacy test was 0.588 and the Bartlett's test was 430.471. The results of goodness of fit indices were not as expected value in the confirmatory factor analysis. In the exploratory factor analysis, it was determined that the factor loadings of the Munro Scale varied between 0.336 and 0.873 and explained 62% of the total variance. In the parallel-form method performed for the reliability of the scale, it was observed that there was a weak and negative correlation between the total scores of the Munro Scale and Braden Scales before the surgery and a negative and moderate correlation between the total scores after the surgery. The total Cronbach's alpha value was found to be 0.504. In the reliability analysis of the scale, interrater correlation coefficients were found to be 0.865-0.998.
Keywords: Munro Scale; Perioperative Period; Pressure Ulcer; Risk Assessment; Validity-reliability